Post cholecystectomy bile duct injury: a surgeon’s nightmare - Sharma, Digvijoy (International Surgery Journal, 2022)
Bile duct injury constitutes a major proportion of morbidity associated with cholecystectomy (laparoscopic>open). It has a lot of impact on patient health and subsequent medico-legal repercussions. Anatomical aberrations in the Calot’s triangle anatomy is more common than meets the eye. A thorough understanding of anatomy, identification of the variant structures, Use of intraoperative cholangiogram and low threshold for conversion to open procedure could prove life-saving in many cases. Optimal timing of intervention has to be planned once the type of injury is identified. Minor leaks are usually managed with endoscopic interventions. More proximal leaks and complete transaction of bile duct usually require Roux En Y hepaticojejunostomy. The principal is to ensure complete drainage of all segments and prevention of sepsis. More grave scenarios like concomitant vascular injury, segmental atrophy and secondary biliary cirrhosis require referral to a tertiary centre and subsequent multidisciplinary approach. The aim of the study was to establish the true incidence, classification and management of bile duct injuries that could be life - saving in a few cases and career- saving in many others.